Mid-career graduate practice outcomes of the James Cook University medical school: key insights from the first 20 years - Tarun Sen Gupta; Torres Woolley; Kath Paton (James Cook University, 2023)
Introduction: Previous studies demonstrate early-career James Cook University (JCU) medical graduates are more likely to practise in regional, rural and remote areas than other Australian doctors. This study investigates whether these practice patterns continue into mid-career, identifying key demographic, selection, curriculum and postgraduate training factors associated with rural practice.Methods: The medical school’s graduate tracking database identified 2019 Australian practice location data for 931 graduates across postgraduate years (PGY) 5-14, which were categorised into Modified Monash Model (MMM) rurality classifications. Multinominal logistic regression was undertaken to identify specific demographic, selection process, undergraduate training and postgraduate career variables associated with practice in a regional city (MMM2), large to small rural town (MMM3-5) or remote community (MMM6-7).Results: One-third of mid-career (PGY5-14) graduates were working in regional cities, mostly in North Queensland, with 14% in rural towns and 3% in remote communities. These first 10 cohorts were undertaking careers in general practice (n=300, 33%), as subspecialists (n=217, 24%), rural generalists (n=96, 11%), generalist specialists (n=87, 10%) or hospital non-specialists (n=200, 22%).Discussion: The findings show positive outcomes from the first 10 JCU cohorts for regional Queensland cities, with a significantly higher proportion of mid-career graduates practising regionally compared with the overall Queensland population. The proportion of JCU graduates practising in smaller rural or remote towns is similar to the overall Queensland population. The establishment of the postgraduate JCUGP Training program and the Northern Queensland Regional Training Hubs for building local specialist training pathways should further strengthen medical recruitment and retention across northern Australia.